2016
DOI: 10.1021/acs.energyfuels.6b02450
|View full text |Cite
|
Sign up to set email alerts
|

Entrapment of Water Droplets in Wax Deposits from Water-in-Oil Dispersion and Its Impact on Deposit Build-up

Abstract: Wax deposition from water-in-oil emulsion/dispersion can entrap water droplets in the resulting paraffin deposits. This entrapment of water droplets can lead to a significant decrease in the yield stress of the deposits, which can cause the deposit to slough-off during wax deposition. This investigation presents the most comprehensive characterization of the entrapment of water droplets by deposit formation with cold finger and flow loop wax deposition experiments. NMR techniques were implemented to characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…If the size of the surface of droplets was larger to some extent compared with these crystals, effective adsorption would be provided . The size of droplets that can be incorporated in the deposition was usually smaller than ∼100 μm, which was claimed by Zhang et al The coarse droplets were hardly dispersed in deposition than fine emulsified droplets. Combined with our research, the maximum diameter of droplets detected from the deposition was 115 μm, demonstrating that the diameter of droplets incorporated into deposition is consistent with former research.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…If the size of the surface of droplets was larger to some extent compared with these crystals, effective adsorption would be provided . The size of droplets that can be incorporated in the deposition was usually smaller than ∼100 μm, which was claimed by Zhang et al The coarse droplets were hardly dispersed in deposition than fine emulsified droplets. Combined with our research, the maximum diameter of droplets detected from the deposition was 115 μm, demonstrating that the diameter of droplets incorporated into deposition is consistent with former research.…”
Section: Resultsmentioning
confidence: 96%
“…The correlation between water content in deposition and water content in emulsion was studied using different apparatuses, cold finger ,, and flow loop, ,, and plotted in the figure with different explanations. Regarding the fact that no obvious relation for both water contents was acquired from experimental results, physical attachment of water droplets to the deposition surface gave rise to the presence of water droplets in deposition, as provided by Kasumu and Mehrotra. , Furthermore, Bruno et al suggested that the water content in deposition is lower than that in the bulk and it increased with the growth of water cut in the bulk.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dispersion is a mixing process caused by the wind waves; this process would cause a liter of dyed water instantaneously released in the ocean to expand and eventually dissipate. [78][79][80][81][82][83][84][85][86] The dispersion occurs in both horizontal and vertical directions. Due to different hydrodynamic processes in each plane, a separate discussion on this topic is necessary.…”
Section: Oil Weathering Processmentioning
confidence: 99%